Relationship of Job Satisfaction with Performance of Contract Nurses In Islamic Hospital of Surabaya - Wijaya, Ika Mardiyanti, Satriya; Mufarrohah, Alinawati Laila; Adriansyah, Agus Aan; Winoto, Priyo Mukti Pribadi; Damawiyah, Siti; Setianto, Budhi (International Journal of Psychosocial Rehabilitation, 2026)
Organizational culture and job satisfaction of nurses’ contract in Islamic Hospital Surabaya is still in standard. This can cause the level of performance of the contract nurses is not optimal, so the impact on the quality of hospital services. Most of the performance of the contract nurses in standard level, but there are some in high levels. The purpose of this research is to analyze the relationship of job satisfaction with performance of the contract nurses. Design research use analytic survey with cross sectional approach. This research population i.e. the whole contract nurses in Islamic Hospital in Surabaya amounted to 86 people. Research samples taken with a cluster sampling method with a large sample of 71 people. The research variables consist of independent variables i.e. job satisfaction and dependent variables i.e. the performance of the contract nurse. Analysis of the data used is a correlation rank spearman test. The results showed mostly (73.2%) Respondents have medium-level job satisfaction, and most (52.1%) Respondents have medium-level performance. The results of the analysis showed there was a significant relationship between job satisfaction and performance of a contract nurse with significance value of 0.001 (< 0.05). The conclusion of this research is the higher job satisfaction nurse contracts, then the higher the performance of nurse contracts. It is recommended that hospitals conduct training on details, skills and skills in working for regular and scheduled contract nurses, rearranging the work environment, evaluating performance and maintaining consistency Hospital policies to improve performance.